Chromosomal characteristics of ribosomal DNA in the primitive semionotiform fish, longnose gar Lepisosteus osseus - Ráb, P; Rábová, M; Reed, K M; Phillips, R B (Chromosome research, 1999)
The chromosomes of longnose gar, Lepisosteus osseus, an extant representative of early radiation of actinopterygian fishes, were studied using conventional Giemsa-staining, Ag-staining, CMA3-fluorescence and fluorescence in-situ hybridization (FISH). The diploid chromosome number was 2n = 56 and the karyotype contained 11 pairs of metacentric, 6 pairs of submetacentric, 3 pairs of subtelocentric macrochromosomes and 16 microchromosomes. Nearly all macrochromosomes showed large CMA3-positive regions resembling the R-bands of higher vertebrates, indicating extensive distribution of GC-rich DNA along chromosomes. The nucleolar organizer regions (NORs) were located on the end of the short arm of a single small metacentric macrochromosomal pair. These sites were strongly CMA3-positive, suggesting that ribosomal sites are associated with GC-rich DNA. In-situ hybridization (FISH) with a rDNA probe gave consistently positive signals in the same regions detected by Ag-staining and CMA3-fluorescence. The evolutionary conservation of positive CMA3-fluorescence of ribosomal sites in 'holostean' and teleostean fishes is discussed.
Keywords: Chromosome Banding; Karyotyping; chromozomy; ryby; Male; DNA, Ribosomal; ribozomální DNA; Ploidies; hybridizace in situ fluorescenční; barvení stříbrem; Animals; Fishes; karyotypizace; Silver Staining; Heterochromatin; zvířata; mužské pohlaví; pruhování chromozomů; Nucleolus Organizer Region; heterochromatin; ženské pohlaví; Female; In Situ Hybridization, Fluorescence; Wisconsin; Chromosomes; organizátor jadérka; ploidie